Pengaruh Likuiditas, Profitabilitas dan Ukuran Perusahaan terhadap Nilai Perusahaan Sub Sektor Perkebunan - Roseliany Dewi, Sufi; Hartono, Hartono (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2025)
The success of a company is reflected in its company value. Increasing market value of company performance due to high stock prices will make the market believe in the company's performance and its prospects in the future. Increasing company profits, maximizing shareholder value are interrelated business goals to achieve goals and to improve shareholder welfare. Price Book Value (PBV) is a measure of value creation to explain stock investment decisions. The purpose of this study is to determine the effect of liquidity, profitability and company size on the value of plantation sub-sector companies listed on the Indonesia Stock Exchange (IDX). The research period is 3 years, namely 2021-2023. The sampling technique uses purposive sampling technique based on the established criteria obtained 7 companies. The data analysis technique used descriptive statistical analysis, classical assumption tests and multiple linear regression analysis processed using SPSS 25 software. Overall, the results of the classical assumption test in this study indicate that it has been fulfilled, among others 1) The residuals of the regression model are normally distributed. 2) The regression model is free from multicollinearity. 3) There is no heteroscedasticity. The research show that 1) Liquidity has no significant effect on company value 2) Profitability has no significant effect on company value 3) Company size has a significant effect on company value 4) Liquidity, Profitability and Company Size simultaneously have a significant effect on company value.